Nation Aging and Development Dilemma - Sebastiana Viphindrartin; - Zainuri (MediaTrend, 2019)
We are attempting to find the effect of nation aging to development in the countries-Japan, China, Brunei, Iran, Cambodia, and Russia. This research employed a quantitative descriptive method and adopted Boston Consulting Group Matrix as the mapping model based on the ratio of shares in the number of the sample countries which is measured by the total percentage. We found that countries with a high growth rate of GDP per population tend to undergo a declining productivity. Demographic factors greatly influence GDP and worth consideration incoming up with sustainable development planning. This paper has contribution to the government to re-derive the policy regarding to nation aging perspective.